Sentir e representar o mundo, escrever as palavras: as manifestações corporais no processo de alfabetização à luz de Henri Wallon - Barreto, Bárbara Travassos (2024)
This research aimed to identify literacy teachers’ views on children’s bodily manifestations during the literacy learning process and the indications of how such views reflect on their practices to develop a proposition for training in context aimed at literacy teachers and rooted in Henry Wallon’s theory, Psychomotricity and the results of this research. It is believed that bodily manifestations are not under children’s control and that literacy teachers must consider them when planning their practices. This qualitative research’s theoretical framework was rooted in Wallonian psychogenetics, and it was performed at a basic education private school in the city of São Paulo. The participants were two teachers who work with 1st and 2nd grades of Elementary school, who responded to a questionnaire. Their classes were observed for 25 hours to raise information on the literacy process. Data analysis was based on prose analysis. Results revealed that planning activities focused on the literacy process must take age range and environment characteristics into account, which includes understanding bodily manifestations as a way to organize thought, relating to themselves and others, and providing a better reading of the world and its situations. Besides, to graphically express what children feel, think, and explore bodily, it is necessary to modulate bodily tensions and distensions. That involves pedagogical intent in choosing the physical space, the possibility of peer interaction, the materials to be used, and the necessary time